Upaya Diplomasi Indonesia melalui Concrete Deliverables pada Presidensi G20 2022 - Haydar, Ahmad Faishal; Utomo, Ario Bimo (Jurnal Ilmiah Hubungan Internasional Fajar, 2025)
Indonesia's G20 Presidency in 2022 marked a significant moment for the country to demonstrate global leadership amid geopolitical tensions and economic uncertainty. This study examines Indonesia's diplomatic efforts through concrete deliverables under the theme "Recover Together, Recover Stronger." By analyzing key outcomes—such as the Bali Leaders' Declaration, the establishment of the Pandemic Fund, and initiatives supporting digital transformation and sustainable energy—this research highlights Indonesia's role in fostering multilateral cooperation. The study employs qualitative methods, including document analysis and expert interviews, to assess how Indonesia navigated complex global challenges while advancing its national interests. Findings suggest that Indonesia successfully leveraged its G20 presidency to strengthen its diplomatic influence, promote inclusive economic recovery, and position itself as a credible mediator in global governance. The research contributes to understanding middle-power diplomacy in multilateral forums and offers insights into Indonesia's evolving role in shaping international policy agendas. Keywords: Indonesia, G20, Diplomacy, Concrete Deliverables